Analysis of the dynamics of paste drying in a spouted bed. Issue 7 (19th May 2019) - Moreira da Silva, Carlos Adriano; Ferreira, Maria do Carmo; Freire, Fabio Bentes; Freire, José Teixeira
Abstract: Although there are some models available in the literature for paste drying in spouted beds, few of them have focused on transient analysis of dynamical systems. Our objective was to integrate experiments and simulations of a dynamic model to investigate the transient response to disturbances and interruptions in the feed flow during paste drying in a spouted bed with inert particles. The spouted bed consisted of a cylindrical column with 50.0 cm of height and 20.0 cm of diameter. Drying tests were performed at inlet gas temperatures of 70 °C and 100 °C and inlet air flow 30% above the minimum spouting velocity. A 5% w/w suspension of calcium carbonate was used as paste material, and glass spheres of 2.2 mm were used as inert materials. Different patterns of step function changes were tested in the paste feed flow rate. A lumped parameter model was used to predict mass and heat transfer during the drying. Experiments and simulations were in good agreement.